Scaling-up dynamics in KOICA's peace-development nexus projects in the Mekong region: Cases of Lao PDR and Cambodia - Bo Kyung Kim; Taekyoon Kim (United Nations Research Institute for Social Development (UNRISD), 2022)
This study investigates the scaling-up dynamics as one form of integrated approach in peacedevelopment nexus projects pursued by the Korea International Cooperation Agency (KOICA) in the Mekong region, with particular reference to Lao PDR and Cambodia. Integrated approaches can be witnessed in various projects using mixed methods that integrate objectives and processes for peace with other dimensions of development such as economic growth and environmental protection. KOICA's mine action and peace village projects in the Mekong region are compelling sites for examining factors shaping the nature and varying degree of scaling-up and integration at the project and programme levels. The shift in approach from project-based to programme-based development in KOICA's operationalization of integrated approach in this region demonstrated diverse pathways for the integration of projects. Multiple and dynamic scaling-up processes enabled the integration in the context of borderlands where authority and ownership are delimited alongside the defensive lines. KOICA's Peace Village Development Projects (PVDP) in borderlands of Mekong region revealed how project or programme develops into more integrated form through horizontal scaling-up, which can be realised through expansion and replication, vertical scaling-up through strengthening capacity and institutions, and functional scaling-up integrating new elements or piggy-back on existing programmes. In Lao PDR and Cambodia, KOICA's PVDPs integrated mine action with comprehensive rural community development through these scaling-up processes, particularly combining existing projects. PVDPs put together the removal of unexploded ordnances and landmines (peace), the protection of human rights of the disabled and mine victims (people) and inclusive rural development (prosperity) in consideration of crosscutting issues of gender and climate change. Needs and capacity assessment as a comprehensive situational analysis for each targeted province and the active involvement of diverse stakeholders such as government agencies and civil society organizations would be key enablers to make a successful design and implementation of the project or programme based on mixed scaling-up processes.
Keywords: 330